Regulation of Photosystem II Heterogeneity and Photochemistry in Two Cultivars of C4 Crop Sugarcane Under Chilling Stress - Mathur, Sonal; Sunoj, Valiaparambil Sebastian John; Elsheery, Nabil Ibrahim; Reddy, Vangimalla R.; Jajoo, Anjana; Cao, Kun-Fang (Frontiers in Plant Science, 2021)
In subtropical regions, chilling stress is one of the major constraints for sugarcane cultivation, which hampers yield and sugar production. Two recently released sugarcane cultivars, moderately chilling tolerant Guitang 49 and chilling tolerant Guitang 28 were selected. The experiments were conducted in the controlled environment and seedlings were exposed to optimum (25/15°C), chilling (10/5°C) and recovery (25/15°C) temperature conditions. PSII heterogeneity was studied in terms of reducing side and antenna size heterogeneity. Under chilling, reducing side heterogeneity resulted in increased number of QB non-reducing centers while antenna side heterogeneity resulted in enhanced number of inactive beta (β) centers in both cultivars, but the magnitude of change was higher in Guitang 49 than Guitang 28. Furthermore, in both cultivars, quantum efficiency of PSII, status of water splitting complex and performance index were adversely affected by chilling, along with reduction in net photosynthesis rate and nigh time respiration and alterations in leaf optical properties. The extents of negative effect on these parameters were larger in Guitang 49 than in Guitang 28. These results reveal a clear differentiation in PSII heterogeneity between differentially chilling tolerant cultivars. Based on our studies, it is concluded that PSII heterogeneity can be used as an additional non-invasive and novel technique for evaluating any type of environmental stress in plants.